ISTRĀTĪJIYYAT MUDARRIS AL-LUGAH AL-ARABIYYAH FĪ TA'LĪM MAHARAH AL-QIRĀ'AH - Akmal Zaid Ramadhani; Faisal Mubarak (UIN ANTASARI, 2020)
Reading is one of the most important language skills in addition to the other three language skills. This is because reading is a means to learn the other world that is desired so that humans can expand their knowledge, have fun, and explore written messages in reading material. Likewise in learning Arabic, reading skills are important skills. Students who take Arabic classes are required to be able to read Arabic texts, both in pronouncing them and in interpreting or understanding the contents of the Arabic texts they read. However, understanding the written text is an activity process that is not easy so that various obstacles are encountered by both students and teachers. Based on these problems, to determine the right strategy, information related to the obstacles experienced is needed. Therefore, the purpose of this study is to describe the obstacles faced and the strategies applied in overcoming these obstacles. The objectives of this study based on the formulation of the problem, namely: (1) Describe the obstacles faced by class XI students in MAN in Banjarmasin, (2) know the strategies of Arabic language teachers in reading skills in MAN Banjarmasin. This study used qualitative research methods. This study uses a descriptive analysis approach, which is a form of data collection. The data collection techniques in this study were interviews and documentation. Interviews were conducted with the Arabic language teacher and five students of class XI from each school. Then the data were analyzed using qualitative descriptive techniques. The results of this study are information on the obstacles faced by students and teachers in terms of linguistic and non-linguistic aspects and the strategies applied by teachers to overcome the obstacles faced. Based on the linguistic review, there were six obstacles faced by students, while for the non-linguistic aspect there were eight obstacles. Of the difficulties faced by the students, the Arabic teacher at MAN 1, 2, and 3 Banjarmasin applied six different strategies to overcome the difficulties of reading Arabic